Studies on the Semen quality of different Veterinary Institutions - THAKUR, SANDEEP; SINGH, MADHUMEET; VASISHTA, N K (The Indian Journal of Animal Reproduction, 2023)
Twenty frozen semen straws of Jersey and IO from Jersey X Red Sindhi crossbred bulls procured from semen processingLaboratory Palampur were evaluated for quality. Equal number of straws from same bulls and batches were evaluated randomlyat different Veterinary institutions of the state. The mean live sperm percentage of Jersey bull semen in frozen thawed strawsfrom semen laboratory was 64-8± 1. 70 as compared to 55. 71±2.43 and 53 . 13±2. 76 in hospitals and dispensaries, respectively.Live sperm percentage of the semen samples from laboratory was significantly higher (p
Keywords: AI; Jersey; crossbred; semen quality